2017
DOI: 10.1172/jci.insight.93683
|View full text |Cite
|
Sign up to set email alerts
|

Human vaccination against Plasmodium vivax Duffy-binding protein induces strain-transcending antibodies

Abstract: BACKGROUND. Plasmodium vivax is the most widespread human malaria geographically; however, no effective vaccine exists. Red blood cell invasion by the P. vivax merozoite depends on an interaction between the Duffy antigen receptor for chemokines (DARC) and region II of the parasite’s Duffy-binding protein (PvDBP_RII). Naturally acquired binding-inhibitory antibodies against this interaction associate with clinical immunity, but it is unknown whether these responses can be induced by human vaccination.METHODS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 64 publications
10
106
0
1
Order By: Relevance
“…There were no serious adverse events (SAEs) or unexpected reactions and no safety concerns during the course of the trial. The reactogenicity of the vaccines was similar to that seen in previous malaria vaccine trials using the same viral vectors at similar doses in healthy adults (37,43,48), with the higher doses of both vaccines associated with an increased number and higher severity of reported AEs (Figure 2). The majority of AEs following ChAd63 RH5 were mild, but moderate AEs were reported by some volunteers in both groups, and 2 volunteers who received the full dose reported severe AEs on the day of vaccination that resolved within 24 hours.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…There were no serious adverse events (SAEs) or unexpected reactions and no safety concerns during the course of the trial. The reactogenicity of the vaccines was similar to that seen in previous malaria vaccine trials using the same viral vectors at similar doses in healthy adults (37,43,48), with the higher doses of both vaccines associated with an increased number and higher severity of reported AEs (Figure 2). The majority of AEs following ChAd63 RH5 were mild, but moderate AEs were reported by some volunteers in both groups, and 2 volunteers who received the full dose reported severe AEs on the day of vaccination that resolved within 24 hours.…”
Section: Resultssupporting
confidence: 75%
“…No data on cellular responses to this antigen have been reported following natural P. falciparum infection; however, given that vaccination elicited peptide-restimulated responses spanning the entire RH5 sequence, the RH5_FL molecule does not appear to lack T cell epitopes. The kinetics and magnitude of the response were also similar to those previously reported following human vaccination with the same vectors encoding P. falciparum or P. vivax antigens (36)(37)(38)(39)43). Similarly, studies using chimpanzee adenovirus vectors followed by MVA boost (44,46,58) have routinely shown that a mixed antigen-specific CD4 + /CD8 + T cell response is induced in humans.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations